2017
DOI: 10.29252/nrip.hdq.2.4.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional Preparedness and Non Structural Safety of Different Health Units of Kermanshah University of Medical Sciences in Coping With Natural Disasters

Abstract: Background: Every year, accidents and disasters occur in Iran and result in death and injuries of common people. People's demand for health care units involves not only the requirement for medical centers but also staffs to work in them. Therefore, the purpose of this study is to investigate the performance readiness and non-structural functional safety of different health care centers and units of Kermanshah University of Medical Sciences in dealing with natural disasters. Materials and Methods:This is a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…There was no significant relationship between the students' awareness and attitudes about food hygiene and safety and other parameters such as age, education level, gender, and faculty [1]. A study on high school students in the USA and students at the University of Missouri demonstrated that the participants had acceptable awareness about the transferrable disease by food [12].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant relationship between the students' awareness and attitudes about food hygiene and safety and other parameters such as age, education level, gender, and faculty [1]. A study on high school students in the USA and students at the University of Missouri demonstrated that the participants had acceptable awareness about the transferrable disease by food [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies on earthquake preparedness that have assessed the readiness of individuals based on their knowledge and skills [11][12][13]. Some studies have also considered structural and nonstructural safety in some cities [14] and some studies have investigated students' readiness [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Past experiences in Iran show that coping with disasters and their complications is a challenge and concern for authorities, and Disaster Management System (DMS) of Iran is always involved in serious problems [1]. Research shows that when a disaster occurs, the pick of medical care needs is within the first 24 hours after the disaster, and 85-95% of the survivals are rescued within first 24 hours [4]. Therefore, in times of crisis, hospitals need to increase their capacity for admission.…”
Section: Introductionmentioning
confidence: 99%